SURVEY OF THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM IN PHYSICAL EDUCATION LEARNING AT PEMANTANGSIANTAR CITY HIGH SCHOOL - Prayogi, Syafi'i; Ibrahim, Ibrahim (Universitas Negeri Medan, 2024)
The aim of this research is to determine the implementation of physical education learning using the independent curriculum, to determine the use of facilities and infrastructure in the physical education learning process using the independent curriculum, the time specified in the physical education learning process using the independent curriculum and the level of success of physical education students using the independent curriculum in Pemantangsiantar City High School. The method used in this research is a survey method. The population used by teachers and students consisted of 3 schools where the names of the schools consisted of Pemantangsiantar 6 Public High School, Pemantangsiantar Exemplary Private High School and Pemantangsiantar East Star Private High School. The instrument used in this research uses a questionnaire, the variable in this research is a survey of the implementation of the independent learning curriculum in physical education learning at Pemantangsiantar City High School and the data analysis technique used is descriptive qualitative and quantitative. The results of the research show that the survey on the implementation of the independent learning curriculum in physical education learning at Pemantangsiantar City High School has a percentage of 88% in the very good category, this percentage was obtained from the percentage of 7 physical education teachers and 160 students. The teacher assessment has a percentage of 85% in the very good category and the percentage of students has a percentage of 88% in the very good category. Because of this, it can be concluded that the survey of the implementation of the independent learning curriculum in physical education learning at Pemantangsiantar City High School has a very good category in accordance with what the researchers wanted.